Litoreibacter roseus sp. nov., a novel bacteriochlorophyll a-containing bacterium. Issue 3 (4th March 2021) - Kanamuro, Masataka; Sato-Takabe, Yuki; Muramatsu, So; Hirose, Setsuko; Muramatsu, Yuki; Takaichi, Shinichi; Hanada, Satoshi
Abstract : A strictly aerobic, bacteriochlorophyll (BChl) a -containing alphaproteobacterium, designated strain K6 T, was isolated from seawater around an aquaculture site in the Uwa Sea in Japan. The novel strain grew optimally at 30 °C at pH 7.0–7.5 and in the presence of 2.0 % (w/v) NaCl. The nonmotile and coccoid or rod-shaped cells formed pink-pigmented colonies on agar plates containing organic compounds. Cells showed an in vivo absorption maximum at 870 nm in the near-infrared region, indicating the presence of BChl a in the light-harvesting 1 complex. The new bacterial strain was Gram-stain-negative and oxidase- and catalase-positive. Phylogenetic analysis based on the 16S rRNA gene sequence showed that strain K6 T was closely related to species in the genus Litoreibacter . The closest phylogenetic relatives of strain K6 T were Litoreibacter ponti GJSW-31 T (98.56 % sequence similarity), Litoreibacter janthinus KMM 3842 T (97.63 %) and Litoreibacter albidus KMM 3851 T (96.88 %). The G+C content of the genomic DNA was 58.26 mol%. The average nucleotide identity value of strain K6 T with the type strain of L. ponti was 77.16 % (SD 4.79 %). The digital DNA−DNA hybridization value of strain K6 T with the type strain of L. ponti was 19.40 %. The respiratory quinone was ubiquinone-10. The major cellular fatty acids were C18 : 1 ω7 c, C16 : 0 and 11-methyl C18 : 1 ω7 c . The dominant polar lipids were phosphatidylcholine and phosphatidylglycerol. On the basis of the genetic and phenotypic data obtained in the present study, we propose a new species in the genus Litoreibacter : Litoreibacter roseus sp. nov., whose type strain is K6 T (=DSM 110109 T =NBRC 114114 T ). Strain K6 T represents the first confirmed species that produces BChl a within the genus Litoreibacter .